Emesis planeca n. comb. (Lepidoptera: Riodinidae): a new combination revealed by molecular evidence with a description of its morphological variation - Trujano-Ortega, Marysol; Callaghan, Curtis J.; García-Vázquez, Uri Omar; Luis-Martínez, Armando; Ávalos-Hernández, Omar; Llorente-Bousquets, Jorge (Zootaxa, 2020)
We transfer Apodemia planeca R. de la Maza E. & J. de la Maza E. 2017 to Emesis as Emesis planeca (R. de la Maza E. & J. de la Maza E.) n. comb. based on phylogenetic hypotheses estimated with one mtDNA and two nDNA markers. This is a rare and poorly known metalmark, endemic to the central region of Balsas Basin in Michoacán, Mexico, originally described from material collected 23 years ago. Here we analyze new specimens from the type locality not included in the original description. With this new material, we describe the morphological variation of adults, including male and female genitalia. This variation is then discussed and compared with the original description. Emesis planeca n. comb. is restricted to the Tropical Deciduous Forest and the adults fly only in the dry season. Due to the spatial, temporal, and ecological rareness of Emesis planeca n. comb., considering it has not been collected in more than two decades and that the Tropical Deciduous Forest is one of the most threatened habitats in Mexico; we propose assigning a protection status to this species.